Effect of Tailwater Height on Flow Performance of Sharp Crested Weir on Downstream Countercurrent in An Open Channel - Mohd Ali, Mohamad Nur Aliff; Mohd Ali, Mas Fawzi; Malik Fesal, Siti Natasha (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Flow over low-head dams was complicated, and dangerous downstream rollers often develop. Particle-based flow visualization, a foundation for the preparatory work, and analysis of counter-current flow on the downstream were conducted. This study is to evaluate the relationship between upstream water level and tailwater height within the downstream counter-current existence. Variation of setup for height over the sharp-crested weir, (h/P) 0.3, 0.4, 0.5, 0.6 and height of tailwater, (tw/P) 0.7, 0.8, 1.0 used. The result for velocity in X-direction for the dowel computed and plotted in contour graph show the different flow patterns and counter-current formation depend on (h/P) and (tw/P).